2020
DOI: 10.1038/s41598-020-77986-z
|View full text |Cite
|
Sign up to set email alerts
|

Voltage and pH difference across the membrane control the S4 voltage-sensor motion of the Hv1 proton channel

Abstract: The voltage-gated proton channel Hv1 is expressed in a variety of cells, including macrophages, sperm, and lung epithelial cells. Hv1 is gated by both the membrane potential and the difference between the intra- and extracellular pH (ΔpH). The coupling of voltage- and ∆pH-sensing is such that Hv1 opens only when the electrochemical proton gradient is outwardly directed. However, the molecular mechanism of this coupling is not known. Here, we investigate the coupling between voltage- and ΔpH-sensing of Ciona in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…In conclusion, the unique voltage and pH gating in the hHv1 channel is based on the spontaneous, voltage-dependent structural transitions of the S4 segment, which facilitate its pH dependent dynamic interactions with both the intra-(H168) and extracellular (H140) pH sensors. Our gating model (Fig 5) also explains the most recent patch-clamp fluorometry data and gating current from Hv channels, which showed that the conformation transitions of the S4 segment are dependent on both intraand extracellular pHs (17,28).…”
Section: Discussionsupporting
confidence: 68%
“…In conclusion, the unique voltage and pH gating in the hHv1 channel is based on the spontaneous, voltage-dependent structural transitions of the S4 segment, which facilitate its pH dependent dynamic interactions with both the intra-(H168) and extracellular (H140) pH sensors. Our gating model (Fig 5) also explains the most recent patch-clamp fluorometry data and gating current from Hv channels, which showed that the conformation transitions of the S4 segment are dependent on both intraand extracellular pHs (17,28).…”
Section: Discussionsupporting
confidence: 68%
“…The intra- and extracellular pHs modify the stability of inward resting conformations by altering the protonation states of the pH-sensing residues that may directly or indirectly interact with the S4 segment in hHv1 channels. The gating model we proposed also explains the most recent patch-clamp fluorometry data and gating current from Hv channels ( Figure 5B ), which showed that the conformation transitions of the S4 segment are dependent on both intra- and extracellular pHs ( Carmona, 2021 ; Schladt and Berger, 2020 ).…”
Section: Discussionsupporting
confidence: 64%
“…ΔpH on H v 1-gating currents unknown. Recently, another report explored the pH sensitivity in the conductive CiH v 1 dimer using patch-clamp fluorometry (21). Tracking the S4 movements with fluorescence changes, they found that the S4 segment sensed the ΔpH imposed on the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the H v 1 pH dependence has been challenging to understand, because it has mainly been studied by measuring the dimer's proton current; in fact, the pH dependence of these currents could be produced by modulating the channel cooperativity, voltage sensor activation, or channel opening. Indeed, there is evidence indicating that pH affects both the voltage sensor movement (20,21) and the channel's unitary conductance (22). Consequently, the simultaneous processes that occur during H v 1 gating obscure the source of this ΔpH dependence.…”
mentioning
confidence: 99%